Optical addressing of nanomechanical metamaterials with subwavelength resolution - Ou, Jun-Yu (2019)
Metamaterials that offer “on-demand” control of individual metamolecules are termed “randomly accessible metamaterials.” They can be useful for manipulation of the wavefront of electromagnetic radiation, for tailoring of the nearfield, and ultimately for multichannel data processing. Here, we demonstrate how light can be used to actuate individual metamaterial elements on demand. Selectivity is achieved by constructing the metamaterial from nanomechanical elements that are designed to have slightly different mechanical resonance frequencies. Actuation is controlled by modulation of the optical control signal at the mechanical resonance frequencies of targeted elements, providing an all-optical route to randomly accessible metamaterials with spatial resolution beyond the diffraction limit.